COMPARATIVE ANALYSIS OF METAPHORS IN UZBEK AND ENGLISH PROVERBS (SCIENCE TIME JOURNAL, 2026)
This article examines metaphorical expressions found in English and Uzbek proverbs and presents a comparative semantic analysis of their figurative structures. Proverbs represent condensed forms of folk wisdom and frequently employ metaphorical imagery to communicate moral principles and social experience. The research focuses on less frequently analyzed metaphors in order to increase originality and highlight unique linguistic features of proverb discourse. The study compares metaphorical models used in the two languages and analyzes their semantic meanings, cultural symbolism, and conceptual domains. The findings demonstrate that English and Uzbek proverbs share universal metaphorical patterns derived from nature, animals, and everyday human activities while simultaneously reflecting unique cultural perspectives. Understanding metaphorical structures in proverbs contributes to the study of cognitive linguistics, comparative linguistics, and intercultural communication.